Dispersal of Late Triassic clam shrimps across Pangea linking northwestern Gondwana and central Pangea rift basins - Alarcón, Carlos M. (2024)
Clam shrimps are a group of freshwater crustaceans who prospered during the Late Triassic. They were abundant in lacustrine sedimentary records of continental basins distributed throughout Pangea during this time. However, they show taxonomic solid differences between the clamp shrimp faunas from the rift basins of central Pangea and the southern Gondwanan basins. In this contribution, we show new fossil clam shrimp assemblages from the lacustrine sedimentary successions of the Eastern Cordillera of Colombia (the Bocas and Montebel formations), providing information on the Late Triassic species that inhabited the northwestern Gondwana basins. This study demonstrates that the basins of northwestern Gondwana shared Norian clamp shrimp species with rift basins of central Pangea and differed in their faunas with the basins of the southern portion of Gondwana. In addition, the Late Triassic clam shrimps paleobiogeographic distribution reflects the dispersal of this fauna throughout fluvial-lacustrine environments established in the rift valleys along the central Pangea. Therefore, the rift valleys produced during the early fragmentation of central Pangea could have acted as corridors for dispersion. Simultaneously, rift valleys also provided paleobiogeographic barriers that isolated the central Pangea clam shrimp faunas from southern Gondwana.